Presence or Absence of Significant HPVE4 Expression in High-grade Anal Intraepithelial Neoplasia With p16/Ki-67 Positivity Indicates Distinct Patterns of Neoplasia: A Study Combining Immunohistochemistry and Laser Capture Microdissection PCR. (April 2018) - Leeman, Annemiek; Pirog, Edyta C.; Doorbar, John; van de Sandt, Miekel M.; van Kemenade, Folkert J.; Jenkins, David; Quint, Wim G.V.
Abstract : Progression of anal intraepithelial neoplasia (AIN) involves transition from productive to transforming human papillomavirus (HPV) infection. Grading aims to distinguish productive low-grade AIN from high-grade anal intraepithelial neoplasia (HGAIN) with risk of cancer. We describe immunohistochemical patterns in AIN adding a novel marker for initiation of the productive phase of the HPV life cycle (panHPVE4) to those for cell cycle activity (Ki-67) and transforming activity of HPVE7 gene (p16). We studied 67 anal biopsies for suspected anal neoplasia (17 normal, 15 AIN1, 20 AIN2, 15 AIN3) from 54 men who have sex with men at New York Presbyterian Hospital, USA. Two pathologists generated consensus AIN and immunogrades. Whole tissue and laser capture microdissection samples from multiple HPV-infected biopsies were tested for HPV with SPF10-PCR-DEIA-LiPA25, version 1. (Para)basal Ki-67 expression distinguished normal from AIN (≥lower-third Ki-67) with sensitivity 0.92 and specificity 1.0. Ki-67 did not distinguish grades of AIN. Null/patchy p16 versus diffuse ≥lower-third patterns discriminated HGAIN (sensitivity, 1.0; specificity, 0.84). There was marked heterogeneity in E4 expression within HGAIN. Most AIN2 (14/20) was E4 + versus 0/15 AIN3 (sensitivity, 0.70; specificity 1.0). HPV was detected in 63 (94%) biopsies, with 49 (77.8%) high-risk HPV + . HPV16 was the most frequent (13%). Multiple HPV genotypes were found in 15 (24%) biopsies and laser capture microdissection -polymerase chain reaction confirmed specific HPV types in E4 +/− AIN. Although Ki-67 discriminated AIN and p16 HGAIN, E4 + /p16 + staining shows that most AIN2 is different from transformed AIN3 in showing both entry into productive HPV infection and transforming activity.